Indispensable role of the oxytocin receptor for allogrooming toward socially distressed cage mates in female mice. (31st May 2021) - Matsumoto, Makiya; Yoshida, Masahide; Jayathilake, Buddhini Wimarsha; Inutsuka, Ayumu; Nishimori, Katsuhiko; Takayanagi, Yuki; Onaka, Tatsushi
Abstract: Social contact reduces stress responses in social animals. Mice have been shown to show allogrooming behaviour toward distressed conspecifics. However, the precise neuronal mechanisms underlying allogrooming behaviour remain unclear. In the present study, we examined whether mice show allogrooming behaviour towards distressed conspecifics in a social defeat model and we also determined whether oxytocin receptor‐expressing neurons were activated during allogrooming by examining the expression of c‐Fos protein, a marker of neurone activation. Mice showed allogrooming behaviour toward socially defeated conspecifics. After allogrooming behaviour, the percentages of oxytocin receptor‐expressing neurones expressing c‐Fos protein were significantly increased in the anterior olfactory nucleus, cingulate cortex, insular cortex, lateral septum and medial amygdala of female mice, suggesting that oxytocin receptor‐expressing neurones in these areas were activated during allogrooming behaviour toward distressed conspecifics. The duration of allogrooming was correlated with the percentages of oxytocin receptor‐expressing neurones expressing c‐Fos protein in the anterior olfactory nucleus, insular cortex, lateral septum and medial amygdala. In oxytocin receptor‐deficient mice, allogrooming behaviour toward socially defeated cage mates was markedly reduced in female mice but not in male mice, indicating the importance of the oxytocin receptor for allogrooming behaviour in female mice toward distressed conspecifics. The results suggest that the oxytocin receptor, possibly in the anterior olfactory nucleus, insular cortex, lateral septum and/or medial amygdala, facilitates allogrooming behaviour toward socially distressed familiar conspecifics in female mice. Abstract : Mice showed allogrooming behaviour towards distressed conspecifics in a social defeat model. Allogrooming behaviour was correlated with activation of oxytocin receptor‐expressing neurones in the anterior olfactory nucleus, insular cortex, lateral septum and medial amygdala. Oxytocin receptor‐deficient females, but not males, showed impairment of allogrooming behaviour, indicating a sexual difference in neural mechanisms of allogrooming.